Public Relations Communication Strategies of PT Semen Padang for Building Corporate Image and Stakeholder Relationships - Relly Anjar Vinata Wisnu Saputra; Tri Nurza Rahmawati (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to analyze the communication strategies of Public Relations (PR) at PT Semen Padang in building corporate image and maintaining relationships with stakeholders. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation of the company’s communication activities. The findings reveal that the PR function is positioned under the Corporate Communication and Secretariat Unit, which is divided into three main sections: household affairs, communication and institutional-external relations, and protocol. In implementing its role, PR categorizes stakeholders based on business processes, including upstream (government and regulatory aspects), operational processes (vendors and private partners), and downstream (distributors and end consumers). The main finding indicates that the communication strategy is predominantly emotional and dialogic, emphasizing mediation as a primary approach in conflict resolution. This strategy is implemented through active involvement in social programs, collaboration with government institutions, and interpersonal engagement with communities and educational institutions. These approaches have proven effective in building a positive corporate image, enhancing stakeholder trust, and ensuring organizational sustainability.